2020
DOI: 10.2147/dmso.s240786
|View full text |Cite
|
Sign up to set email alerts
|

<p>Artemether Regulates Metaflammation to Improve Glycolipid Metabolism in db/db Mice</p>

Abstract: Background: Artemether, a commonly used artemisinin derivative, has been shown to possess potential antidiabetic activities. However, only limited information is available on the mechanisms of artemether in type 2 diabetes. Therefore, in this study, we examined some of the possible mechanisms of artemether (ATM) upon glycolipid metabolism in the db/db mouse model of diabetes. Materials and Methods: Male C57BL/KsJ-db/db and C57BL/KsJ-db/+ mice at 4 weeks of age were divided into four groups (N=6/group): ( 1) NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…Rates of weight gain↓food and water intake↓ fasting blood glucose levels↓GTT and ITT (improved) islet function, insulin resistance and insulin sensitivity (improved) serum lipid levels (TC, TG and FFA)↓ islet vacuolar degeneration and hepatic steatosis (improved) AMPK↑ GLUT-4↑ IRβ↑ expression of inflammatory factors↓ Fu et al (Fu et al, 2020) Frontiers in Pharmacology | www.frontiersin.org…”
Section: Overview Of Artemisinin and Its Derivativesmentioning
confidence: 99%
See 4 more Smart Citations
“…Rates of weight gain↓food and water intake↓ fasting blood glucose levels↓GTT and ITT (improved) islet function, insulin resistance and insulin sensitivity (improved) serum lipid levels (TC, TG and FFA)↓ islet vacuolar degeneration and hepatic steatosis (improved) AMPK↑ GLUT-4↑ IRβ↑ expression of inflammatory factors↓ Fu et al (Fu et al, 2020) Frontiers in Pharmacology | www.frontiersin.org…”
Section: Overview Of Artemisinin and Its Derivativesmentioning
confidence: 99%
“…Therefore, the crucial goals for treating T2DM are mainly to improve IR and islet cell function. In Fu’s research, islet function and IR were significantly improved in male db/db mice treated for 4 weeks with 100 mg/kg or 200 mg/kg artemether ( Fu et al, 2020 ). Many studies have shown that artemisinin and its derivatives have great potential in the treatment of T2DM, whether in the early stage or late stage of the disease.…”
Section: Type 2 Diabetesmentioning
confidence: 99%
See 3 more Smart Citations